До проблеми назви Київського таємного товариства 40-х рр. XIX ст. як відображення його ідеології та мети діяльності - Симоненко, Р. (Історіографічні дослідження в Україні, 1998)
Till now the above-mentioned Kyiv Secret Society was known - almost exclusively - as “Cyril and Methodius Society”. But does this definition reflects precisely the role of this Secret Society as the first national political organisation and the founder of the modem Ukrainian ideology and movement? The author examines arguments in favour of equal use for the name of the Kyiv Secret Society also the another original definition - “Ukrainian-Slavic Society” - as the adequate reflection of the ideology and the aims of this secret national organisation.